Political beliefs affect compliance with government mandates - Painter, Marcus; Qiu, Tian (Journal of economic behavior & organization, 2021)
We use the state-mandated stay-at-home orders during the coronavirus pandemic as a setting to study whether political beliefs inhibit compliance with government orders. Using geolocation data sourced from smartphones, we find residents in Republican counties are less likely to completely stay at home after a state order has been implemented relative to those in Democratic counties. Debit card transaction data shows that Democrats are more likely to switch to remote spending after state orders are implemented. Heterogeneity in factors such as Covid-19 risk exposure, geography, and county characteristics do not completely rule out our findings, suggesting political beliefs are an important determinant in the effectiveness of government mandates. Political alignment with officials giving orders may partially explain these partisan differences.